Opportunities for Implementing Inclusive Education in Primary School - Sevinch, Gadoyeva (Journal of Innovation in Education and Social Research, 2025)
This article analyzes the theoretical and practical foundations of implementing an inclusive approach in the primary education system. It outlines the main principles of inclusive education, the role of teachers, opportunities for creating an adapted learning environment, and scientific perspectives on the psychological development and social integration of students with special educational needs. The article also highlights the prospects for developing inclusive education in the education system of Uzbekistan, existing challenges, and ways to overcome them.